Diagnosis of community capacities and resources in the Alberto Spencer Sectoral Committee, Santa Elena canton, Ecuador (Gestionar: revista de empresa y gobierno, 2023)
The diagnosis of community capacities and resources arises as an essential need in the management of sectoral or neighborhood development, considered as a component of vital importance for communities. The purpose of this research was to diagnose the types of community capacities and resources in the Alberto Spencer sector committee, Santa Elena canton. Based on this research work, a mixed approach was used, which allows for describing, analyzing, and studying the reality within the sector framework. The population of this research includes the members of the committee and the inhabitants of the Alberto Spencer sector, Santa Elena canton. The method employed to obtain the sample was probabilistic sampling. The study period for this research extends from May 2021 to January 2022. Data collection involved in-depth interviews and surveys conducted with the community members who played a central role in this research. The results were presented after being processed using descriptive statistical methods, which facilitated their interpretation. It is possible to conclude that it is emphasized that the committee should develop projects in collaboration with the inhabitants of the sector in order to promote a sense of collectivity within the community. This is essential to address the demands of the environment, particularly by utilizing the community capacities and resources available in the sector. The participation of the community is highly recommended as part of this process. Consequently, the diagnosis constitutes a fundamental step for local and community development in the sector.
Keywords: diagnosis; capacities; committee; citizen participation; resources